Juridicial Review of Rights of Mental Disabilities In Procurement of Civil Servants - Risang Pujiyanto; Sonny Taufan (UNIFIKASI : Jurnal Ilmu Hukum, 2021)
This study aims to examine and analyze the rights of persons with mental disabilities in the procurement of Civil Servants. This research is a normative research using the statute approach. The results of the study found that the disabilities types in Act Number 5/2014 concerning State Civil Apparatus include persons with physical disabilities, deaf and blind people, which are different from the disability types set out in Act Number 8/2016. The difference in disability types is due to Act Number 5/2014 issued at the time Act Number 4/1997 concerning Disabled Persons is still in effect, and this implies that the mental disability rights to apply for Civil Servants are not yet accommodated.